FRI0589 CLINICAL ACCURACY OF ANTI-PHOSPHATIDYLSERINE/PROTHROMBIN AND ANTI-BETA2GLYCOPROTEIN I DOMAIN I FOR PREDICTING CLINICAL MANIFESTATIONS OF ANTIPHOSPHOLIPID SYNDROME. (2nd June 2020) - Radin, M.; Cecchi, I.; Foddai, S. G.; Rubini, E.; Barinotti, A.; Sciascia, S.; Roccatello, D.
Abstract : Background: Antiphospholipid antibody (aPL) specificities are increasing, however the best accuracy for predicting the clinical manifestations of the diseases is still under debate. Objectives: To evaluate the clinical accuracy of aPL specificities both individually and/or in combination, to identify a panel of tests that may provide the best accuracy for predicting clinical manifestations of antiphospholipid syndrome (APS). Methods: We chart-reviewed patients that presented at San Giovanni Bosco Hospital in the last 5 years who tested persistently positive for at least one aPL[1]. Inclusion criteria comprehended: a)Primary APS(PAPS); b) Secondary APS(SAPS), c)aPL positive asymptomatic and d)Patients with clinical manifestations of APS and either inconsistent previous LA positivity and/or low-medium titers aPL(suspect APS). Results: A total of 122 patients were included in the study 38 PAPS, 31 SAPS, 23 aPL positive asymptomatic and 30 low titers APS patients). Table1 resumes the main clinical and laboratory characteristics of the patients included in the study. All patients were tested for five aPL: criteria aPL, anti-phosphatidylserine/prothrombin(aPS/PT) and anti-Beta2Glycoprotein I Domain I(β2GPI-D1). Among the single aPL positivity, β2GPI-D1 showed the best accuracy in predicting the clinical manifestations of APS (AUC 0.639, CI95% 0.539–0.74, p=0.011). Similarly, when investigating the possible combinations of aPL panels, the positivity for aPS/PT IgG/IgM and/or β2GPI-D1 showed the best accuracy in predicting the clinical manifestations of APS (AUC 0.698, CI95%0.604 –0.793, p<0.001) while triple criteria aPL IgG positivity had the best accuracy for predicting recurrences (AUC 0.720, CI95% 0.569–0.871, p=0.012). Results of the ROC curves are illustrated in Figure 1 . When considering aPL asymptomatic patients and APS patients (both PAPS and SAPS), the only two aPL combinations that showed a statistically significant association with the APS group were aPS/PT IgG/IgM and/or β2GPI-D1 (OR 4.86, CI95%1.76-13.3, p<0.05) and Global APS Score >11 (OR 2.87, CI95% 1.08-7.6, p<0.05). Interestingly, also adding the patients with suspect APS to the equation, the combination of aPS/PT IgG/IgM and/or β2GPI-D1 remained statistically significant (OR 2.5, CI95%1.02-7.05 p<0.05). Conclusion: Combining anti-β2GPI D1 and aPS/PT improves the diagnostic power of aPL testing and might improve in risk stratification in patients with aPL positivity. References: [1] Miyakis S et al. International consensus statement on an update of the classification criteria for definite antiphospholipid syndrome (APS). J Thromb Haemost [Internet]. 2006 Feb;4(2):295–306. Disclosure of Interests: None declared